2011
DOI: 10.5194/acp-11-4577-2011
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic aerosols may have increased upper tropospheric humidity in the 20th century

Abstract: Abstract. Recent simulations of deep convection with a spectral microphysics cloud model show that an increase in aerosol concentration can have a significant effect on the nature of convection with more ice precipitation and less warm rain in polluted air. The cloud lifetime and the area covered by cloud anvils of deep convection are also larger for polluted air. Therefore, it is possible that the increase of anthropogenic aerosols in most of the 20th century has increased humidity and perhaps also cloudiness… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Rosenfeld et al, 2007) and increasing the stratiform ice water content (de Boer et al, 2010;D. Rosenfeld & Lensky, 1998), anvil longevity (Tulet et al, 2010), and cloud top height (Bister & Kulmala, 2011). However, it is still unclear whether aerosols could influence the total volume of rainfall (TRV) produced during the entire lifetime of these MCSs.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenfeld et al, 2007) and increasing the stratiform ice water content (de Boer et al, 2010;D. Rosenfeld & Lensky, 1998), anvil longevity (Tulet et al, 2010), and cloud top height (Bister & Kulmala, 2011). However, it is still unclear whether aerosols could influence the total volume of rainfall (TRV) produced during the entire lifetime of these MCSs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Data and methods 2.1 Data UTH, i.e. the relative humidity with respect to water, in a layer between approximately 200 and 500 hPa, was obtained from the microwave humidity sounder (MHS; Bonsignori, 2007) on board the MetOp-A satellite for 60 • S to 60 • N. The ascending node was used, crossing the Equator northward at 21:30 local solar time. A microwave method developed by Buehler et al (2008) enabled us to detect relative humidities also in the areas of anvil clouds.…”
Section: Introductionmentioning
confidence: 99%
“…4,5] have found that clouds produce more extensive anvils in the presence of high aerosol loading. Bister and Kulmala [6] propose that aerosols could affect the amount of water vapour left in the upper troposphere after deep convection due to their effect on cloud microphysics leading to more ice precipitation and less warm rain.…”
Section: Aerosols May Increase Upper Tropospheric Humidity Introductionmentioning
confidence: 99%